2021
DOI: 10.3390/nano11123421
|View full text |Cite
|
Sign up to set email alerts
|

Improved Light Harvesting of Fiber-Shaped Dye-Sensitized Solar Cells by Using a Bacteriophage Doping Method

Abstract: Fiber-shaped solar cells (FSCs) with flexibility, wearability, and wearability have emerged as a topic of intensive interest and development in recent years. Although the development of this material is still in its early stages, bacteriophage-metallic nanostructures, which exhibit prominent localized surface plasmon resonance (LSPR) properties, are one such material that has been utilized to further improve the power conversion efficiency (PCE) of solar cells. This study confirmed that fiber-shaped dye-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…They concluded that the interactions were fundamental for their assembly. Additionally, Koo et al [ 28 ] demonstrated that the absorbance spectrum changes when M13 phages were embedded with silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the interactions were fundamental for their assembly. Additionally, Koo et al [ 28 ] demonstrated that the absorbance spectrum changes when M13 phages were embedded with silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…However, since conventional FDSSCs contain an electrolyte in a liquid state, stability of the power conversion efficiency (PCE) of the solar cells is very unstable due to leakage and volatility of the electrolyte. Hence, in our previous studies, solid-state FDSSCs (SS-FDSSCs) were developed with PCE comparable to liquid electrolytebased devices and excellent stability that were not seen in liquid electrolyte [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%